The potential mechanism of celastrol attenuating atherosclerosis by promoting macrophage autophagy via AMPK/ULK1 pathway - Li, Jiao; Zhao, Yanrong; Qi, Yanfang; Chen, Yafang; Liu, Yue; Fang, Linlin; Zhou, Zhenying; Wei, Liping; Li, Qi (Frontiers in Pharmacology, 2025)
BackgroundThis study aimed to elucidate the molecular mechanisms by which celastrol (Cel) alleviates atherosclerosis (AS) through the regulation of macrophage autophagy.MethodsAn AS model was established using ApoE−/− mice fed a high-fat diet. Mice in the treatment group received Cel. Aortic plaque formation, lipid metabolism, inflammatory responses, and autophagy activation were evaluated via histopathological analysis, serological assays, immunofluorescence staining, transmission electron microscopy, and Western blotting. In vitro, macrophages were transformed into foam cells using oxidized low-density lipoprotein (ox-LDL) and treated with various concentrations of Cel.ResultsCel markedly reduced aortic plaque formation, ameliorated dyslipidemia, attenuated inflammatory responses, and enhanced plaque stability in ApoE−/− mice. It significantly promoted macrophage autophagy, as evidenced by increased autophagy-related markers and autophagosome formation. Mechanistically, Cel-induced autophagy was mediated by the AMPK/ULK1 pathway, and this effect was reversed by the AMPK inhibitor Compound C.ConclusionCel exerts anti-atherosclerotic effects by activating macrophage autophagy via the AMPK/ULK1 pathway, thereby improving lipid metabolism, reducing inflammation, and stabilizing plaques. These findings highlight the therapeutic potential of Cel and provide new insights into autophagy-targeted strategies against AS.